2014
DOI: 10.1111/apt.12730
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: gluten may cause depression in subjects with non‐coeliac gluten sensitivity – an exploratory clinical study

Abstract: SUMMARYBackground Current evidence suggests that many patients with self-reported non-coeliac gluten sensitivity (NCGS) retain gastrointestinal symptoms on a gluten-free diet (GFD) but continue to restrict gluten as they report 'feeling better'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
82
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 44 publications
5
82
1
2
Order By: Relevance
“…5 This may also be the case in NCGS subjects who exhibit low levels of somatisation while on a GFD, 6 with Peters et al subsequently demonstrating blinded gluten exposure to induce a state of depression. 1 These findings are similar to that seen in coeliac disease where depression is commonly reported, 7 and a GFD in symptomatic individuals leads to an improvement in perception of health and psychological well-being. 8 How does the current study tie in with the literature?…”
supporting
confidence: 77%
See 1 more Smart Citation
“…5 This may also be the case in NCGS subjects who exhibit low levels of somatisation while on a GFD, 6 with Peters et al subsequently demonstrating blinded gluten exposure to induce a state of depression. 1 These findings are similar to that seen in coeliac disease where depression is commonly reported, 7 and a GFD in symptomatic individuals leads to an improvement in perception of health and psychological well-being. 8 How does the current study tie in with the literature?…”
supporting
confidence: 77%
“…Peters et al 1 explore the relationship between gluten ingestion and mental state in individuals with noncoeliac gluten sensitivity (NCGS). Following a randomised, placebo-controlled, double-blind, cross-over, dietary re-challenge study, the authors conclude that gluten may induce feelings of depression and that 'feeling better' on a gluten-free diet (GFD) may be a consequence of psychological, rather than intestinal, well-being.…”
mentioning
confidence: 99%
“…Only coeliac disease, dermatitis herpetiformis and ataxia syndromes have a reasonable to high level of evidence in their immunological response and pathophysiology. An example of the difficulties in defining the offending agents is the recent demonstration that carbohydrate-depleted gluten induced current feelings of depression in a randomised controlled re-challenge study [10]; the challenged agent used was 70% gluten, and it cannot be concluded that gluten caused the effect. Thus, it is essential to address the complexity of wheat both by examining its other components and by addressing how gluten might induce problems by mechanisms other than specific immune responses (as in coeliac disease).…”
Section: Evidence Base For Gluten Causing Non-coeliac Effectsmentioning
confidence: 99%
“…Furthermore, the effects of wheat/gluten are clearly heterogeneous with several pathogenic pathways involving or independent of inflammation likely. This is best illustrated by the range of events from wheat allergy syndromes [15] to coeliac disease [16] to wheat sensitivity with eosinophilic gut infiltration [9] to gluten-induced feeling of depression where no markers of inflammation or gluten-related immune phenomena exist [10]. …”
Section: Evidence Base For Gluten Causing Non-coeliac Effectsmentioning
confidence: 99%
See 1 more Smart Citation